If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 5(x + -3) = 2(2x + 1) Reorder the terms: 2 + 5(-3 + x) = 2(2x + 1) 2 + (-3 * 5 + x * 5) = 2(2x + 1) 2 + (-15 + 5x) = 2(2x + 1) Combine like terms: 2 + -15 = -13 -13 + 5x = 2(2x + 1) Reorder the terms: -13 + 5x = 2(1 + 2x) -13 + 5x = (1 * 2 + 2x * 2) -13 + 5x = (2 + 4x) Solving -13 + 5x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 5x + -4x = 2 + 4x + -4x Combine like terms: 5x + -4x = 1x -13 + 1x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + 1x = 2 + 0 -13 + 1x = 2 Add '13' to each side of the equation. -13 + 13 + 1x = 2 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = 2 + 13 1x = 2 + 13 Combine like terms: 2 + 13 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| 17=k+1 | | 7x+3.4=-1.5 | | p(5)=10x-7 | | -2x-12=7-3x | | X+6=x^3 | | 5(2x+4)-3(x+2)= | | 18+11x=23 | | 5x-7x+4=3-3x | | 6(x+1)=w | | -8(g+3)=-56 | | 6x-5=7-11x | | -51=2y+19-3y | | -1(z+17)=20 | | X^3-x-6=0 | | -545=20k-5 | | 5(2x+4)=40 | | 2(x-4)-10= | | -12x-11=25-11(x-1) | | 2x+3y-9=0 | | X+17=10-3x | | 14+19=13d-1 | | 12x^3=48 | | 14d+19=13-1 | | x^3+7x^2-2x=-1 | | x+(y-5)=31 | | x+(x-5)=31 | | 6x^4y^4-6x^3y^2+8xy^2-8= | | x^4+15x^2+56=0 | | 7x+6x+4+9=5x+5+7x | | -25x^2+36=-25x | | 5.37+x=8.4 | | 6t^2-t+5= |